2020
DOI: 10.31234/osf.io/htny8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in Maternal Substance Use During the COVID-19 Pandemic

Abstract: Background: Maternal stress levels and mental health symptoms have significantly increased since the coronavirus (COVID-19) pandemic began. As a result, experts have become concerned about elevated substance use given well-known associations between negative emotions and increased substance use. Extant research has not examined substance use among mothers during the COVID-19 pandemic which is a critical next step given links between maternal substance use and adverse childhood outcomes. Methods: Data was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…These results suggest that efforts to ensure economic security may help address parents’ and other caregivers’ mental health needs and reduce adverse parenting risk. Studies also noted more couple conflict [50] and increased substance use [51] among parents and caregivers experiencing stress and anxiety during the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that efforts to ensure economic security may help address parents’ and other caregivers’ mental health needs and reduce adverse parenting risk. Studies also noted more couple conflict [50] and increased substance use [51] among parents and caregivers experiencing stress and anxiety during the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen of the included studies present results from cross-sectional surveys (Myran 2020;Canadian 2020;Currie 2021;Dozois 2021;Dumas et al 2020;Farhoudian et al 2020;Imtiaz et al 2021;Joyce et al 2020;Prowse et al 2021;Rotterman 2020;Rotterman 2021;Statistics 2021;Turna 2021;Turna et al 2021;Turner 2019;Vedelago et al 2022;Zajacova et al 2020). The remaining four include an ecological study (Canadian 2021), a conceptual model (Enns et al 2020), a prospective cohort study (Leatherdale et al 2021), and a longitudinal study (Bartel et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining four include an ecological study (Canadian 2021), a conceptual model (Enns et al 2020), a prospective cohort study (Leatherdale et al 2021), and a longitudinal study (Bartel et al 2020). Eighteen studies were conducted solely in Canada (Canadian 2021;Myran 2020;Canadian 2020;Currie 2021;Dozois 2021;Dumas et al 2020;Imtiaz et al 2021;Joyce et al 2020;Prowse et al 2021;Rotterman 2020;Rotterman 2021;Statistics 2021;Turner 2019;Vedelago et al 2022;Zajacova et al 2020;Enns et al 2020;Leatherdale et al 2021;Bartel et al 2020), and the remaining three studies included global data, including Canadian data (Farhoudian et al 2020), data from Canada and the United States (US) (Turna et al 2021), or data collected from Canada, US, Brazil, and Italy (Turna 2021). A summary of the scoping review study data can be found in Table3 and characteristics of included studies can be found in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside of the United States, SU in pregnant women is similarly prevalent across Europe (Göransson et al., 2003), Australia (Passey et al., 2014), and Africa (Bifftu, 2020). Furthermore, during the current coronavirus (COVID‐19) pandemic, the incidence of maternal SU may rise, especially in anxious mothers (Joyce et al., 2020). While prenatal substance exposure is concerning for the child, including associations with low birth weight and behavioral and intellectual deficits (Bailey et al., 2012; Black et al., 2013), it is also important to recognize that maternal SU postpartum may have consequences for child development—which may have an additive or interactive effect with prenatal exposures (Hatzis et al., 2017; Molitor & Mayes, 2010; Porreca et al., 2018; Punamäki et al., 2021).…”
Section: Introductionmentioning
confidence: 99%